Improving Our Knowledge on the 229mThorium Isomer: Toward a Test Bench for Time Variations of Fundamental Constants. Issue 5 (11th February 2019) - Thirolf, Peter G.; Seiferle, Benedict; von der Wense, Lars
Abstract: For more than four decades, the lowest excitation in the whole landscape of atomic nuclei, the low‐lying, isomeric state of 229 Th, the so‐called thorium isomer, has challenged physicists of various disciplines. Being a solitaire with its uniquely low excitation energy of <10 eV, its predicted lifetime of a few hours results in an extremely sharp relative linewidth Δ E / E as low as 10 –20 . While until recently the indication of its existence was based only on indirect evidence, its unique properties inspired a multitude of potential applications, like the use of the thorium isomer as a nuclear frequency standard, potentially able to outperform even the best atomic clocks and a sensitivity‐enhanced access to potential temporal variations of fundamental constants. The various proposals to exploit the unique properties of 229m Th are presented herein, in particular focusing on its ability to serve as a test bench for time variations of fundamental constants like the fine structure constant. Abstract : The first excited state of thorium‐229 is introduced as candidate for an ultraprecise nuclear frequency standard. Applications for a "nuclear clock" are given, from improved accuracy of satellite‐based navigation to geodesy, dark matter search, or to an enhanced sensitivity for temporal variations of fundamental constants. Recent achievements toward exploiting 229m Th as a test bench for fundamental physics are reviewed.